Graphene-based plasmonic waveguide devices for electronic-photonic integrated circuit. (October 2018) - Kim, Jin Tae; Choe, Jong-Ho; Kim, Jin-Soo; Seo, Dongjea; Kim, Young Duck; Chung, Kwang Hyo
Highlights: Architecture of graphene electronic-photonic integrated circuits is proposed. Characteristics of graphene-based plasmonic waveguide devices are investigated. Perspectives on the graphene-based plasmonic waveguide devices are presented. Abstract: Graphene is a one-atom thick carbon film packed in a honeycomb structure, and because it has extraordinary optoelectronic properties, it has attracted a great deal of attention in the field of photonics. Graphene-based plasmonic photonic devices have been developed which are capable of emitting, transmitting, modulating, and detecting light wave signals using a single material. In this paper, we propose the concept of on-chip graphene electronic-photonic integrated circuits (EPICs) architecture, and present developments and perspectives on the essential graphene plasmonic-based photonic components, including the plasmonic waveguide, modulator, and photodetector, which are based on the graphene EPICs. The optical characteristics and design considerations of the graphene-based photonic devices are discussed based on experimental and theoretical investigations at telecommunications wavelengths. In parallel, we provide new device design concepts and a potential solution for further improving their operating characteristics. We also performed a numerical investigation of the characteristics of the photonic devices to explain their operating principles and to predict their operating performances. The proposed photonic components were fabricated on an organic photonic chip using an optimized fabrication process, and their optical characteristics were experimentally demonstrated. Based on these results and demonstrations, we hope to introduce new perspectives on the future direction of graphene-EPICs in graphene plasmonics and the optical telecom field.